Desigualdade e cidadania: uma leitura a partir dos deficientes visuais do Rio de Janeiro - Natália Pacheco Junior (Ciências Sociais Unisinos)
To get a better understanding of the social insertion of blind people in the contemporary city, I developed a research project that is divided in two axes: The first one discusses the evolution of the public debate about the rights of this minority; the second one explores three case studies of visually disabled persons and their social integration in the city of Rio de Janeiro. Initially I describe the literal and substantive transformation of the Brazilian laws that refer to blind people to get subsidies to make a critical analysis of their history as citizens in Brazil. Then I present the educational careers of three blind persons in order to evaluate the implementation of those laws in their daily routines and to see whether they are visible to the blind persons and their families. All the cases appoint to a lack of social support by the institutions and to the fact that different kinds of citizenship are not seen as a problem in our society. The article shows that the laws related to visually disabled people aren´t sufficient to create an equitable society in Brazil.